KEWENANGAN POLISI LALU LINTAS KOTA SAMARINDA MELAKUKAN RAZIA DI JALAN BEDASRKAN PERATURAN PEMERINTAH NOMOR 80 TAHUN 2012 - Eka Safi’i Nuriyanto (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTThe number of people who still cannot understand the role, the obligation of traffic police to do rajia, I chose the title "The Traffic Authority of Samarinda City Traffic Raiding on the Road Based on Government Regulation Number 80 of 2012" so that the public understands the authority of traffic police. Legal research conducted in this study Using the Normative Juridical approach is believed to be a decision analysis so that the expected results are obtained. Law enforcement officers (traffic police) act as deterrents and as actresses in political functions. In addition, the traffic police also carry out the regeling function (for example, regulation of the obligations for certain motorized vehicles to supplement with safety triangles) and functions specifically in the case of permits or beginstiging (for example, issuing a driver's license). Government Regulation No. 80 of 2012 concerning the inspection of motorized vehicles and the enforcement of traffic violations and road transport is the basis of the authority of traffic police to carry out raids on road vehicles and the role of the police as law enforcers. The role of the police in the context of law enforcement must be based on applicable rules and the code of ethics of the police themselves.Keywords: Traffic Police, Examination, Enforcement, Violations